Schema Activation in Literary Interpretation: A Study on the Words of Wisdom in Tuesdays with Morrie - Ditha Prameswari; Dhuha Hadiyansyah (UniversitasAl Azhar Indonesia, 2025)
Literary works often convey moral lessons that invite readers to reflect on life experiences. However, few studies have examined how readers interpret such messages through a psycholinguistic lens.This research explores how students interpret Morrie Schwartz’s words in Mitch Albom’s Tuesdays with Morrie through the framework of Schema Theory. Using a qualitative approach, data were collected from semi-structured interviews with 16 students of the English Language and Culture Department at University of Al-Azhar Indonesia. Informants were presented with 20 selected quotes and asked to choose those most meaningful to them, explain their feelings, and reflect on the relevance to their lives. The findings reveal that the most memorable quotes were “Learn to forgive yourself and to forgive others,” “Love wins. Love always wins,” and “Life is a series of pulls back and forth. …”. These quotes activated language schema (simplicity and clarity of expression), content schema (personal experiences and values), and formal schema (use of repetition, parallelism, or paradox). By contrast, less chosen quotes, such as those on aging, were not relatable to the students’ current experiences. The study highlights the significance of Schema Theory in psycholinguistic analysis of literature, showing how readers connect language, structure, and personal knowledge to create meaning.Keywords – Psycholinguistics, Schema Theory, Tuesdays With Morrie